Pengaruh Komitmen Organisasi, Kepuasan Kerja Dan Budaya Organisasi Terhadap Organizational Citizenship Behavior: Studi Pada PT Victoria Insurance - Jihan Adelia Putri; Andi Fariana (Jurnal Manajemen dan Ekonomi Kreatif, 2024)
Organizational citizenship behavior (OCB) is the behavior of employees who consciously and voluntarily carry out work outside of their job description and several studies show that many factors cause the emergence of OCB in employees. For this reason, in this research we try to analyze the influence of organizational commitment, job satisfaction and organizational culture on OCB, namely by conducting a special study on PT employees. Victoria Insurance. This research method uses quantitative methods with a total of 42 samples taken. Data processing uses SPSS version 25.0, where validity and reliability testing uses the Pearson product moment test and Cronbach Alpha statistics. The data collection technique used is a questionnaire technique. The analytical method for answering the hypothesis uses multiple linear regression analysis. Based on the research results, it shows that the organizational commitment variable has a positive and significant effect on organizational citizenship behavior (OCB), job satisfaction has no effect on organizational citizenship behavior (OCB) while organizational culture has a positive and significant effect on organizational citizenship behavior (OCB). Adjusted R Square is 0.927, which means that organizational citizenship behavior (OCB) is influenced by Organizational Commitment, Job Satisfaction and Organizational Culture with a percentage of 92.7% and the remaining 7.3% is influenced by other factors outside this research.